2013
DOI: 10.1530/eje-13-0166
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of primary somatostatin analogue therapy and pituitary adenomectomy on survival in patients with acromegaly: a retrospective cohort study

Abstract: Objective: Acromegalic patients have an increased risk of mortality. The objective of this study was to compare the effect of different therapies for acromegaly on mortality. Design and methods: The mortality rate of 438 consecutive acromegalic patients was compared with that of the general population using the standardized mortality ratio (SMR); the effect of different therapies on survival was evaluated using Cox regression analysis. Results: Twenty patients (4.5%) died between 1999 and 2009. Age-and sex-adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
5
39
0
Order By: Relevance
“…A recent meta-analysis by Holdaway et al (7) has demonstrated that studies with O30% utilization of SSAs or O70% of remission rates reported normal life expectancy in contrast to higher mortality rates in those with lower percentages of SSA administration and remission rates. In line with these findings, the Campania cohort had a normal life expectancy -an SMR of 0.66 (95% CI 0.27-1.36; PZ0.269) in agreement with two recent studies concerning mortality among the Italian population (33,34,35). Owing to funding restrictions in Bulgaria, SSAs and GHRAs were not available in clinical practice until 2008 and none of the patients were under such Table 5 Characteristics of patients in the three treatment groups.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…A recent meta-analysis by Holdaway et al (7) has demonstrated that studies with O30% utilization of SSAs or O70% of remission rates reported normal life expectancy in contrast to higher mortality rates in those with lower percentages of SSA administration and remission rates. In line with these findings, the Campania cohort had a normal life expectancy -an SMR of 0.66 (95% CI 0.27-1.36; PZ0.269) in agreement with two recent studies concerning mortality among the Italian population (33,34,35). Owing to funding restrictions in Bulgaria, SSAs and GHRAs were not available in clinical practice until 2008 and none of the patients were under such Table 5 Characteristics of patients in the three treatment groups.…”
Section: Discussionsupporting
confidence: 86%
“…Some research groups reported even lower GH targets: 2 mg/l by Ayuk et al and a further improvement in mortality when GH was reduced to !1 mg/l (23,26). Indeed, the last GH value (or post-glucose GH (30)) has been ascertained as a strong predictor of mortality by uniand multivariate analyses in various surveys (23,26,27,33,35). In agreement, the last GH value was an independent predictor of mortality in our study as well (Table 4).…”
Section: Clinical Studysupporting
confidence: 86%
See 3 more Smart Citations